7
$\begingroup$

Given the sequence $(X_n), n=1,2,... $, of iid exponential random variables with parameter $1$, define:

$$ M_n := \max \left\{ X_1, \frac{X_1+X_2}{2}, ...,\frac{X_1+\dots+X_n}{n} \right\} $$ I want to calculate $\mathbb{E}(M_n)$. Running a simulation leads me to believe that $$ \mathbb{E}(M_n)=1+\frac{1}{2^2}+\cdots+\frac{1}{n^2} = H_n^{(2)}.$$ Is this correct? If yes, how would one go proving it? I tried using induction and the fact that $M_{n+1}=\max \{M_n, \frac{1}{n}(X_1+\cdots+X_{n+1}) \}$ along with the equality $E(X_1|X_1+\cdots+X_{n+1})=\frac{1}{n}(X_1+\cdots+X_{n+1})$ but didn't manage to accomplish anything.

$\endgroup$
6
  • $\begingroup$ Cute problem. I doubt your conjecture is true as $$E(M_{n}-M_{n-1})=\frac 1{n}P(M_{n}=\frac {S_{n}}n)$$ But for $n\ge 3$, $P(M_n=S_1)>P(X_1=\max_{i\le n} X_i)=\frac 1 n$ and heuristically $P(M_n=\frac {S_i}i)$ is a non-increasing function of $i\le n$, so $P(M_n=\frac {S_n}n)<\frac 1 n$, so your conjecture is an upper bound only. $\endgroup$ – A.S. Dec 16 '15 at 23:31
  • $\begingroup$ @A.S. The correct formula should be the 2nd order $n^{\rm th}$ harmonic number , rather than the first order $n^2-{\rm th}$ harmonic number. $\endgroup$ – heropup Dec 17 '15 at 1:28
  • $\begingroup$ My heuristic was wrong. $P(M_3=\frac {S_3}3)=\frac 1 3$ in alignment with conjecture. $\endgroup$ – A.S. Dec 17 '15 at 3:24
  • $\begingroup$ that looks very much like that the $E[\cdot]$ here. Possibly relevant links: 1 2 $\endgroup$ – BCLC Dec 17 '15 at 14:28
  • $\begingroup$ @A.S. Really 1/3 and not $H_3^{(2)}$ ? $\endgroup$ – BCLC Dec 17 '15 at 15:35
4
$\begingroup$

For any $x>0$ and $n>1$, the following relation holds (with $\mathbb P(M_1\leqslant x)=1-e^{-x}$):

$$ \mathbb P(M_n \leqslant x)=\mathbb P(M_{n-1} \leqslant x) - e^{-nx}\frac{x^{n-1}n^{n-2}}{(n-1)!}\tag{1} $$

Consequently, $\mathbb P(M_n \leqslant x) = 1 - \sum\limits_{r=1}^{n} e^{-rx} \frac{x^{r-1}r^{r-2}}{(r-1)!}$. Therefore,

$$\mathbb E[M_n]=\int\limits_{0}^{\infty} \mathbb P(M_n>x) \mathrm dx = \sum\limits_{r=1}^{n}\int\limits_{0}^{\infty}e^{-rx}\frac{x^{r-1}r^{r-2}}{(r-1)!}\mathrm dx = \sum\limits_{r=1}^{n}\frac{1}{r^2}\,.$$


Proof of $(1)$:

$$ \mathbb P(M_{n-1} \leqslant x) - \mathbb P(M_n \leqslant x) = e^{-nx}\int\limits_{0}^{x}\int\limits_{0}^{2x-x_1}\ldots\int\limits_{0}^{(n-1)x-\sum_{i=1}^{n-2}x_i}\mathrm dx_{n-1} \ldots \mathrm dx_1 \\= e^{-nx}\frac{x^{n-1}n^{n-2}}{(n-1)!}\,, $$ where the volume integral may be evaluated by successive application of Leibniz's integral rule .

$\endgroup$
1
  • $\begingroup$ Can you explain a bit how Leibniz's integral rule can be used to prove $(1)$? $\endgroup$ – mr.stealyourgirl Dec 21 '15 at 15:54
3
$\begingroup$

One way to calculate $EM_n$ is to first calculate $P(M_n>m)$, for $m\in \mathbb R$, then use $EM_n=\int_0^\infty P(M_n>m)\,dm$.

Note that, in order for the event $\{M_n\le m\}$ to occur, it must be true that $X_1\le m$ and $X_2\le 2m-X_1$, and $X_3\le 3m-X_2-X_1$, and so on. Thus,

$$P(M_n\le m) = \int_0^m\int_0^{2m-x_1}\int_0^{3m-x_1-x_2}\cdots \int_0^{nm-x_1-\dots-x_{n-1}}e^{-(x_1+x_2+\cdots x_n)}dx_n\,dx_{n-1}\,\cdots dx_1\tag{*}$$

You can now use this expression to calculate $EM_n$. For example,

$$P(M_2\le m) = \int_0^me^{-x_1}\int_0^{2m-x_1}e^{-x_2}\,dx_2\,dx_1=\int_0^me^{-x_1}-e^{-2m}\,dx_1=1-me^{-2m}-e^{-m}$$ so, $$EM_2=\int_0^\infty P(M_2>m)\,dm=\int_0^\infty me^{-2m}+e^{-m}\,dm=\frac14+1$$ This does seem to suggest that $EM_n=\sum_1^n \frac1{k^2}$.

It might get messy, but perhaps you deduce a formula for $P(M_n\le m)$ by looking at more small cases, then prove it is correct by induction.

$\endgroup$
0

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.